The Relationship Between Leadership Styles And Trainers’ Job Satisfaction In Adama Tvet College Of Oromia Regional State - Kebede Bultuma (My University, 2015)
The general objective of this study was to assess the relationship between Leadership styles and full-time Trainers’ job satisfaction at Adama TVET College in Adama City Administration of Oromia Regional State. The whole TVET College, 14 college leaders and 95 trainers’ members, of the chosen TVET College was defined as the sample. A descriptive correlation research design and Cross-sectional survey type was employed. To select the samples a combination purposive, nonproportional stratified and simple random sampling techniques were used. The data was collected in March and April, 2015 by using MLQ and JSS. The findings highlight that trainers were moderately satisfied. The transformational leadership style, in relation to the other two independent variables (transactional and laissez-faire leadership styles) is the dominant leadership, and has a weak positive and no statistically significant effect on college trainers’ overall job satisfaction. Whereas, the transactional leadership style is the second, relatively, has weak positive and statistically insignificant effect on College trainers’ overall job satisfaction. On the other hand, laissez-faire leadership has comparatively weak negative and statistically insignificant effect on TVET College Trainer’s overall job satisfaction. In addition, the educational qualification and age demographic factor are also weak positive predictor on the Overall job satisfaction while the Sex and Work experience are a negative predictor of trainers overall job satisfaction. Therefore, the current rate of trainer turnover experienced within Adama TVET College is not only due to incorrect usage of leadership styles but also demographic factors matter. Adama TVET College suggested to adopt a TF leadership style but has to use a mix of transactional managerial abilities with a paper dose of and transformational abilities. Therefore, Adama TVET College leaders need to avoid any laissez-faire behavior and spend time instead coaching, paying attention to employees’ desires, abilities and needs, help them develop their talent, and provide a supportive environment. This would help achieve minimize trainers turn over and higher performance standard within the college.
Keywords: Educational Planning